THE INTERPRETATION OF SYEIKH HAJI MUHAMMAD SA’ID BIN UMAR IN TAFSEER NUR AL-IHSAN AND SAYYID QUTB IN TAFSEER FI ZHILALIL QUR’AN ON RUQYAH’S VERSES (At-Tibyan, 2023)
The goals of this study are to describe the concept of "ruqyah," know about the educational backgrounds of both the two commentators, and determine how the two commentators' interpretation of their Tafseer connects to the verses of ruqyah. For this literature review, the writer performs library research to collect books or information significant to the topic. This conceptual and theoretical study of the literature from previous research is the key focus of this study. The researcher is using a comparative approach (muqarnas) to analyze the data, which comprises compiling, analyzing, and comparing both commentators' interpretations of ruqyah from the perspective of the Qur'an. According to the research results, ruqyah is the process of reading authentic Qur'anic verses and Allah's attributes well with intention of treating one's situation by Islamic law (based on authentic history or the provisions agreed upon by the scholars). To provide care of sick people, to protect ourselves, to seek Allah SWT for healing from problems, or to seek protection.